Chronobiology differs between men and women with cluster headache, clinical phenotype does not. (14th March 2017) - Lund, Nunu; Barloese, Mads; Petersen, Anja; Haddock, Bryan; Jensen, Rigmor
Abstract : Objective: To describe differences between the sexes in the phenotype of cluster headache (CH) in a large, well-characterized clinical CH population. Methods: Patients from the Danish CH survey aged 18–65 years, diagnosed with CH according to International Classification of Headache Disorders, second edition, completed questionnaires and structured interviews. Results: A total of 351 patients with CH participated, with a male:female ratio of 2:1. The diurnal variation of attacks showed moments of peak prominence in men's attack cycle to be advanced by 1 hour compared to women's, despite no difference in self-reported bedtime or chronotype ( p = 0.31). The onset of CH decreased with increasing age for both sexes. Diagnostic delay was numerically longer for men vs women (6.56 vs 5.50 years, p = 0.21); however, more women had previously been misdiagnosed (61.1% vs 45.5%, p < 0.01) and received the correct diagnosis at a tertiary headache center (38.8% vs 20.9%, p < 0.001). Only minor sex differences in clinical characteristics were found but chronic CH was more prevalent in women compared to men (44.0% vs 31.9%, p < 0.05). Conclusions: Despite a similar clinical phenotype, diurnal attack cycle is advanced by 1 hour in men with CH compared to women. Rhythmicity is a defining characteristic of CH and these findings suggest differences in the hypothalamus' influence on attack occurrence between the sexes. In addition, women were more often misdiagnosed and diagnosis in the primary or secondary sector more often failed. Furthermore, women had chronic CH more frequently than men. A long diagnostic delay and frequent misdiagnosis emphasize the need for increased awareness of CH in both sexes.